1975
DOI: 10.2307/1942329
|View full text |Cite
|
Sign up to set email alerts
|

A Population of Great Basin Pocket Mice, Perognathus parvus, in the Shrub‐Steppe of South‐Central Washington

Abstract: A population of Great Britain pocket mice, Perognathus parvus, was live—trapped in 1967—72 on a 2.7—ha study area in south—central Washington to determine their density, reproductive performance, longevity, movements, and home range, as well as their functional role in northern shrub—steppe habitat. During 41,310 trap—nights we captured 15,386 mice representing seven species: Perognathus parvus, Peromyscus maniculatus, Onychomys leucogaster, Reighrodontomys megalotis, Lagurus curtatus, Microtus montanus, and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1978
1978
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…In fact, Merriam's kangaroo rats rarely reach densities Ͼ20/ha, and they do seem to be strongly food limited (Soholt 1973, Zeng and Brown 1987, Brown and Heske 1990, Nagy and Gruchacz 1994. Second, population densities of granivorous desert rodents respond quickly to annual changes in the seed crop, with little carryover to subsequent years (O'Farrell et al 1975, Nelson and Chew 1977, Brown and Heske 1990, Price and Kelly 1994. This suggests that each year's seed production, rather than the more stable seed bank, determines fecundity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Merriam's kangaroo rats rarely reach densities Ͼ20/ha, and they do seem to be strongly food limited (Soholt 1973, Zeng and Brown 1987, Brown and Heske 1990, Nagy and Gruchacz 1994. Second, population densities of granivorous desert rodents respond quickly to annual changes in the seed crop, with little carryover to subsequent years (O'Farrell et al 1975, Nelson and Chew 1977, Brown and Heske 1990, Price and Kelly 1994. This suggests that each year's seed production, rather than the more stable seed bank, determines fecundity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…June captures were often very different in number and species composition than August-September captures since some species, such as thirteen-lined ground squirrel, hibernate early (Carey et al 2003), while others, for example, Perognathus spp., have late season peaks of abundance (O'Farrell et al 1975). June captures were often very different in number and species composition than August-September captures since some species, such as thirteen-lined ground squirrel, hibernate early (Carey et al 2003), while others, for example, Perognathus spp., have late season peaks of abundance (O'Farrell et al 1975).…”
Section: Mammal Monitoring and Data Analysismentioning
confidence: 99%
“…The western harvest mouse Reithrodontomys megalotis was the third most abundant small mammal caught on the trapping grids. O'Farrell et al (1975) thought harvest mice typical only of riparian vegeta-tion, though later studies found them to be the second most abundant small mammal in cheatgrass-dominated old fields (Gano et al, 1983). Consistent with the latter finding, the present study found harvest mice only in burned (cheatgrass) habitats and in spiny hopsage-Sandberg's bluegrass habitats (see Fig.…”
Section: Mammalsmentioning
confidence: 99%